A device and method for preparing nano silver powder by electrolytic refining

By using anion exchange membrane in electrochemical method to separate the electrolyte cells, combining acidic and weakly alkaline electrolytes, internal circulation and Ag+ supplementation are achieved, and the low yield and unsustainable production of nano silver powder preparation in the prior art are solved. The problem of this paper achieves efficient and low-cost nano silver powder preparation.

CN118345456BActive Publication Date: 2025-02-25KUNMING UNIV OF SCI & TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410503621.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-25
Publication Date
2025-02-25
Estimated Expiration
2044-04-25

AI Technical Summary

Technical Problem

In the prior art, the preparation of nano silver powder by electrochemical method has the problem of complex additives, low yields and inability to produce sustained production.

Method used

The electrolytic cell is separated into an anode chamber and a cathode chamber. The anode chamber uses acidic electrolyte and soluble crude silver anode, and the cathode chamber uses weakly alkaline electrolyte and stainless steel or titanium plate cathode to realize internal circulation and Ag+ supplementation.

Benefits of technology

The yield and current efficiency of silver powder are improved, and an efficient, continuous and low-cost one-step preparation from coarse silver to nano silver powder is achieved. The obtained silver powder has a uniform particle size and regular morphology.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118345456B_ABST
    Figure CN118345456B_ABST
Patent Text Reader

Abstract

The present invention discloses a device and method for preparing nano silver powder by electrolytic refining, and relates to the technical field of nano silver powder preparation. An anion exchange membrane is used to separate an electrolytic cell into an anode chamber and a cathode chamber. The anode chamber is filled with a silver nitrate solution, and the cathode chamber is filled with a silver ammonia solution. The anode of the electrolytic cell is a soluble anode, and the cathode is a stainless steel or titanium plate. The electrolyte in the electrolytic cell is electrolyzed by constant current. During the electrolysis process, the electrolyte in the cathode chamber is separated and the silver powder is collected before entering the anode chamber. The electrolyte in the anode chamber is separated from impurities before entering the cathode chamber, so as to realize the internal circulation of the electrolyte. Using anion diaphragm electrolysis, the anode chamber uses an acidic electrolyte to thicken the silver anode, which can continuously replenish Ag to the system. + The cathode chamber uses a weak alkaline electrolyte plus a stainless steel or titanium plate cathode to prevent the nano silver powder from dissolving back, increase the silver powder yield, and make it easier to obtain spherical silver powder with uniform particle size in the silver ammonia solution medium.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nano silver powder preparation, and in particular to a device and a method for preparing nano silver powder by electrolytic refining. Background Art

[0002] Nanosilver powder is widely used in electronics, new energy, medical and other industrial fields as a catalyst, conductive electric shock material and antimicrobial agent. In recent years, with the development of technology, the demand for nanosilver powder has been increasing, but due to the limitations of preparation technology, domestic production capacity has not increased much and relies on imports.

[0003] There are two methods for preparing nano silver powder: physical method and chemical method. Physical method includes mechanical ball milling, evaporation condensation, laser ablation, atomization, DC arc plasma, etc. However, physical method has problems such as high purity of raw materials and large equipment investment, which makes it difficult to apply on a large scale. Chemical method mainly includes liquid phase chemical reduction method and electrochemical deposition method. Liquid phase chemical reduction method is to add reducing agent and dispersant to silver source solution to make Ag + Direct reduction to solution, this method is simple and controllable, and has become the mainstream method for preparing nano silver powder at home and abroad, but this method produces a large amount of organic wastewater, and the silver powder is easily wrapped by organic matter, resulting in a decrease in the quality of the silver powder. Electrochemical deposition method occupies an important position in the production of nano powders, and has many advantages including: simple process, low requirements for raw material purity, low investment, and controllable product particle size and morphology.

[0004] At present, the electrolyte system for preparing nano silver powder by electrochemical method can be divided into two types: acidic and alkaline. When using the acidic system, the current efficiency is extremely low, less than 10%, mainly because the nano silver powder is highly active and easily oxidized and dissolved, and the addition of various additives leads to aggravated hydrogen evolution, so it is not widely used. When using the alkaline system, although the current efficiency can be greatly improved, it is difficult to use soluble crude silver as the anode, and the commonly used inert anode is more expensive, and the Ag in the electrolyte is too high. +The fluctuation range is large, and it is difficult to continuously produce qualified nano silver powder. Patent CN114540881A discloses a method for preparing micron-scale monodisperse silver powder based on electrochemical deposition. Its additives are complex, and the obtained silver powder particle size is coarse, which is difficult to reach the size of nano silver powder. Patent CN102418118A discloses a method for electrochemically assisted preparation of special morphology silver powder, which uses an inert anode. Silver ions are continuously reduced during the electrodeposition process, which is difficult to produce sustainably. Patent CN101314860A discloses a method for preparing nano silver powder, which is dissolved by the anode of a metal silver electrode in a single-chamber electrolytic cell, with an inert conductive material as the cathode, and a room temperature ionic liquid containing a silver salt as the electrolyte. Through direct current electrolysis, nano silver powder is reduced at the cathode, but the ionic liquid is expensive and not suitable for large-scale application, and coarse silver cannot be used as an anode in a single-chamber electrolytic cell, otherwise the silver ion replenishment rate is lower than the reduction rate, resulting in a continuous reduction of silver ions in the electrolyte, so only a high-purity anode can be used, and the one-step preparation of coarse silver to nano silver powder cannot be achieved. Summary of the invention

[0005] The object of the present invention is to provide a device and method for preparing nano silver powder by electrolytic refining, so as to solve the problems of complex additives, low yield and unsustainable production in the prior art.

[0006] In order to solve the above technical problems, the present invention adopts the following technical scheme: a method for preparing nano silver powder by electrolytic refining, characterized in that: an anion exchange membrane is used to separate an electrolytic cell into an anode chamber and a cathode chamber, the anode chamber is filled with a silver nitrate solution, the cathode chamber is filled with a silver ammonia solution, the anode of the electrolytic cell is a soluble anode, and the cathode is a stainless steel or titanium plate. The electrolyte in the electrolytic cell is subjected to constant current electrolysis. During the electrolysis process, the electrolyte in the cathode chamber is separated and silver powder is collected and then enters the anode chamber, and the electrolyte in the anode chamber enters the cathode chamber after impurities are separated, so as to realize the internal circulation of the electrolyte.

[0007] A further technical solution is that the anion exchange membrane is a polystyrene disulfonate membrane or a polyethylene sulfonate membrane.

[0008] A further technical solution is that the pH value of the silver nitrate solution is controlled at 1-2 by nitric acid, the pH value of the silver ammonia solution is controlled at 7-8 by ammonia water, and the cathode chamber Ag + The concentration is 2-10 g / L, Ag in the anode chamber + The concentration is higher than that of Ag in the cathode chamber + concentration.

[0009] A further technical solution is to add polyvinyl pyrrolidone as a dispersant to the silver ammonia solution at a concentration of 0.1 to 1 g / L, and apply ultrasonic oscillation in the cathode chamber.

[0010] A further technical solution is that the cathode current density is controlled to be 20-50 mA / cm 2 , the electrolysis temperature is 60-70℃.

[0011] A further technical solution is that the device for preparing nano silver powder by electrolytic refining adopted in the method comprises an electrolytic cell, wherein the electrolytic cell is divided into an anode chamber and a cathode chamber by an anion exchange membrane, the lower outlet of the anode chamber is connected to a cathode liquid buffer tank through a filter, the cathode liquid buffer tank is connected to an upper inlet of the cathode chamber, the upper outlet of the cathode chamber is connected to an anode liquid buffer tank through a filter, and the anode liquid buffer tank is connected to an upper inlet of the anode chamber.

[0012] A further technical solution is that the bottom outlet of the cathode liquid buffer tank is connected to a waste electrolyte tank.

[0013] Reaction mechanism:

[0014] Anode main metal dissolution: Ag-e=Ag+

[0015] Anode impurity dissolution: M-ne=M n+ (M represents impurity metals such as Zn, Fe, Pb, Cu, etc.)

[0016] Cathode silver reduction: [Ag(NH3)2] + +e+2H2O=Ag+2NH4 + +2OH -

[0017] Cathode impurity reduction: The standard electrode potential of other metal impurities is lower than that of silver, so they are not precipitated at the cathode.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] 1) The present invention innovatively uses anion diaphragm electrolysis, and the anode chamber uses an acidic electrolyte and a thickened silver anode to continuously replenish Ag to the system. + The cathode chamber uses a weak alkaline electrolyte plus a stainless steel or titanium plate cathode to prevent the nano silver powder from dissolving back, increase the silver powder yield, and make it easier to obtain spherical silver powder with uniform particle size in the silver ammonia solution medium.

[0020] 2) The system temperature is controlled at 60-70°C, which can not only promote the formation of spherical silver powder, but also alleviate the pore clogging problem of the anion exchange membrane caused by crystallization.

[0021] 3) Ultrasonic oscillation and dispersants can promote the timely shedding of silver powder on the cathode plate and evenly disperse it in the electrolyte, thereby avoiding the intensification of hydrogen evolution caused by the increase in the electrochemical specific surface area of ​​the cathode, thereby improving the current efficiency.

[0022] 4) The electrolyte circulation and proper opening can alleviate the Ag in the cathode chamber. + concentration changes, while avoiding the accumulation of impurity ions in the system and reducing the amount of wastewater.

[0023] 5) Compared with the existing liquid phase reduction method and electrochemical deposition method, this method has simple process, high yield and low energy consumption, and realizes the efficient, continuous and low-cost one-step preparation from crude silver to nano silver powder. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 It is a structural schematic diagram of the present invention.

[0025] Figure 2 This is a scanning electron microscope image of the silver powder obtained by diaphragm electrolysis in Example 1 of the present invention.

[0026] Figure 3 This is a scanning electron microscope image of the silver powder obtained by electrolysis in Example 2 of the present invention.

[0027] Figure 4 This is a scanning electron microscope image of the silver powder obtained by electrolysis in Example 3 of the present invention.

[0028] Figure 5 This is a scanning electron microscope image of the silver powder obtained by electrolysis in Comparative Example 1.

[0029] Figure 6 This is a scanning electron microscope image of the silver powder obtained by electrolysis in Comparative Example 2. DETAILED DESCRIPTION

[0030] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0031] Example 1

[0032] The diaphragm electrolyzer is a domestic polystyrene disulfonate membrane. The diaphragm separates the electrolyzer into an anode chamber and a cathode chamber. The electrolyte volume of the cathode chamber and the anode chamber is 1L. The electrolyte of the anode chamber is a silver nitrate solution. + The concentration is 20g / L, pH=1 (adjusted by nitric acid), the cathode electrolyte is silver ammonia solution, Ag + The concentration is 5g / L, pH=7 (adjusted by ammonia water), NH4 + The concentration is controlled at NH4 + / Ag +(molar ratio) is greater than 1, polyvinyl pyrrolidone (PVP) is added as a dispersant at 0.5 g / L, ultrasonic oscillation is applied to the cathode chamber, the electrolysis temperature is controlled at 60°C, the anode is a coarse silver sheet with a purity of 97.13%, the cathode is a titanium plate, and the effective working area is 10 cm 2 , the cathode current density is controlled at 20mA / cm 2 .

[0033] The device used in the above method is as follows Figure 1 As shown, it includes an electrolytic cell, in which an anion exchange membrane separates the electrolytic cell into an anode chamber and a cathode chamber, the lower outlet of the anode chamber is connected to a cathode liquid buffer tank through a filter, the cathode liquid buffer tank is connected to an upper inlet of the cathode chamber, the upper outlet of the cathode chamber is connected to an anode liquid buffer tank through a filter, and the anode liquid buffer tank is connected to an upper inlet of the anode chamber.

[0034] The electrolyte circulation is as follows: the electrolyte in the anode chamber continuously flows out from outlet A, and after filtering out the floating anode mud through filter A, enters the cathode liquid buffer tank (effective volume 10L) through inlet A, and then flows out through outlet C, and enters the cathode chamber through inlet C. The electrolyte in the cathode chamber flows out from outlet D, collects the silver powder through filter B, and then enters the anode liquid buffer tank (effective volume 10L) through inlet D, and then flows out from outlet E, and enters the anode chamber through inlet E. The entire electrolyte circulation flow rate is 52.08mL / h. After one cycle, 0.5L is opened from outlet B of the cathode liquid buffer tank to enter the waste electrolyte tank for treatment, and the corresponding electrolyte is replenished in the cathode chamber and the anode chamber.

[0035] The key indicators of the electrolysis are shown in Table 1. The electrolysis can be operated continuously for at least two weeks with a current efficiency of 97.05% and a silver powder yield of 0.7812 g / h. A total of 262.48 g of nano silver powder was obtained in two weeks with a purity of 99.92%. Figure 2 As shown, the silver powder particle size is about 100 nm and is spherical.

[0036] Table 1 Key indicators for the preparation of nano silver powder in Example 1

[0037]

[0038] Example 2

[0039] The diaphragm electrolyzer is a domestic polystyrene disulfonate membrane. The diaphragm separates the electrolyzer into an anode chamber and a cathode chamber. The electrolyte volume of the cathode chamber and the anode chamber is 1L. The electrolyte of the anode chamber is a silver nitrate solution. + Concentration 30g / L, pH = 1.5 (adjusted by nitric acid), the cathode electrolyte is silver ammonia solution, Ag + The concentration is 7g / L, pH=7.5 (adjusted by ammonia water), NH4+ The concentration is controlled at NH4 + / Ag + (molar ratio) is greater than 1, polyvinyl pyrrolidone (PVP) is added as a dispersant at 0.1 g / L, ultrasonic oscillation is applied to the cathode chamber, the electrolysis temperature is controlled at 65°C, the anode is a coarse silver sheet with a purity of 97.13%, the cathode is a titanium plate, and the effective working area is 10 cm 2 , cathode current density is controlled at 35mA / cm 2 .

[0040] The device used in the above method is as follows Figure 1 As shown, it includes an electrolytic cell, in which an anion exchange membrane separates the electrolytic cell into an anode chamber and a cathode chamber, the lower outlet of the anode chamber is connected to a cathode liquid buffer tank through a filter, the cathode liquid buffer tank is connected to an upper inlet of the cathode chamber, the upper outlet of the cathode chamber is connected to an anode liquid buffer tank through a filter, and the anode liquid buffer tank is connected to an upper inlet of the anode chamber.

[0041] The electrolyte circulation is as follows: the electrolyte in the anode chamber continuously flows out from outlet A, and after filtering out the floating anode mud through filter A, enters the cathode liquid buffer tank (effective volume 10L) through inlet A, and then flows out through outlet C, and enters the cathode chamber through inlet C. The electrolyte in the cathode chamber flows out from outlet D, collects the silver powder through filter B, and then enters the anode liquid buffer tank (effective volume 10L) through inlet D, and then flows out from outlet E, and enters the anode chamber through inlet E. The entire electrolyte circulation flow rate is 59.85mL / h. After one cycle, 0.5L is opened from outlet B of the cathode liquid buffer tank to enter the waste electrolyte tank for treatment, and the corresponding electrolyte is added to the cathode chamber and the anode chamber.

[0042] The key indicators of the electrolysis are shown in Table 2. The electrolysis can be operated continuously for at least two weeks with a current efficiency of 97.73% and a silver powder yield of 1.3766 g / h. A total of 462.54 g of nano silver powder was obtained in two weeks with a purity of 99.90%. Figure 3 shown.

[0043] Table 2 Key indicators for the preparation of nano silver powder in Example 2

[0044]

[0045] Example 3

[0046] The diaphragm electrolyzer is a domestic polystyrene disulfonate membrane. The diaphragm separates the electrolyzer into an anode chamber and a cathode chamber. The electrolyte volume of the cathode chamber and the anode chamber is 1L. The electrolyte of the anode chamber is a silver nitrate solution. + Concentration 50g / L, pH = 2 (adjusted by nitric acid), the cathode electrolyte is silver ammonia solution, Ag +Concentration is 10g / L, pH=8 (adjusted by ammonia water), NH4 + The concentration is controlled at NH4 + / Ag + (molar ratio) is greater than 1, polyvinyl pyrrolidone (PVP) is added as a dispersant at 1g / L, ultrasonic oscillation is applied to the cathode chamber, the electrolysis temperature is controlled at 70°C, the anode is a coarse silver sheet with a purity of 97.13%, the cathode is a titanium plate, and the effective working area is 10cm 2 , cathode current density is controlled at 50mA / cm 2 .

[0047] The device used in the above method is as follows Figure 1 As shown, it includes an electrolytic cell, in which an anion exchange membrane separates the electrolytic cell into an anode chamber and a cathode chamber, the lower outlet of the anode chamber is connected to a cathode liquid buffer tank through a filter, the cathode liquid buffer tank is connected to an upper inlet of the cathode chamber, the upper outlet of the cathode chamber is connected to an anode liquid buffer tank through a filter, and the anode liquid buffer tank is connected to an upper inlet of the anode chamber.

[0048] The electrolyte circulation is as follows: the electrolyte in the anode chamber continuously flows out from outlet A, and after filtering out the floating anode mud through filter A, enters the cathode liquid buffer tank (effective volume 10L) through inlet A, and then flows out through outlet C, and enters the cathode chamber through inlet C. The electrolyte in the cathode chamber flows out from outlet D, collects the silver powder through filter B, and then enters the anode liquid buffer tank (effective volume 10L) through inlet D, and then flows out from outlet E, and enters the anode chamber through inlet E. The entire electrolyte circulation flow rate is 49.21mL / h. After one cycle, 0.5L is opened from outlet B of the cathode liquid buffer tank to enter the waste electrolyte tank for treatment, and the corresponding electrolyte is added to the cathode chamber and the anode chamber.

[0049] The key indicators of the electrolysis are shown in Table 3. The electrolysis can be operated continuously for at least two weeks with a current efficiency of 97.81% and a silver powder yield of 1.97 g / h. A total of 661.92 g of nano silver powder was obtained in two weeks with a purity of 99.89%. Figure 4 shown.

[0050] Table 3 Key indicators for the preparation of nano silver powder in Example 3

[0051]

[0052] Comparative Example 1

[0053] A non-diaphragm electrolytic cell was used, the electrolyte was silver nitrate solution, 5g / L, pH=1, 0.5g / L PVP was added as a dispersant, ultrasonic waves were applied at the same time, the electrolysis temperature was controlled at 60°C, the anode was a coarse silver sheet with a purity of 97.13%, the cathode was a titanium plate, and the effective working area was 10cm 2, the cathode current density is controlled at 20mA / cm 2 , because there is no diaphragm, the electrolyte does not circulate.

[0054] The key indicators of the electrolysis are shown in Table 4. The current efficiency is only 8.91% and the silver powder yield is 0.072g / h when using diaphragm-free electrolysis. It can only run for 15h at most and obtain 1.08g of silver powder with a purity of 99.89%. Figure 5 As shown, the particle size is relatively coarse, about 300-600nm, and the morphology is irregular.

[0055] Table 4 Key indicators for the preparation of nano silver powder in Comparative Example 1

[0056]

[0057]

[0058] Comparative Example 2

[0059] The non-diaphragm electrolytic cell is used, and the electrolyte is silver ammonia solution. + 5g / L, pH=8, 0.5g / LPVP was added as a dispersant, and ultrasonic waves were applied at the same time. The electrolysis temperature was controlled at 60°C. Because a weak alkaline electrolyte was used, crude silver could not be used as a soluble anode. The anode was a platinum sheet, the cathode was a titanium plate, and the effective working area was 10cm 2 , the cathode current density is controlled at 20mA / cm 2 , because there is no diaphragm, the electrolyte does not circulate.

[0060] The key indicators of the electrolysis are shown in Table 5. Although the current efficiency and yield are similar to those in Example 1, the electrolysis without diaphragm is not as good as that in Example 1. + The anode can only be operated for 5 hours at most, and the platinum sheet is used as an inert anode, and the anode can only produce oxygen evolution, which leads to an increase in cost and useless energy consumption. Figure 6 As shown, due to the obvious fluctuation of silver ions, a large amount of coarse-grained silver powder was produced.

[0061] Table 5 Key indicators for the preparation of nano silver powder in comparative example 2

[0062]

[0063] The difference between using a diaphragm electrolytic cell and a single-chamber electrolytic cell can be seen from Comparative Examples 1 and 2 and Examples 1, 2 and 3. Obviously, the diaphragm electrolytic cell in the present method can run continuously for a longer time, and the obtained silver powder is of higher quality and has a higher yield.

[0064] Although the present invention is described herein with reference to a number of illustrative embodiments of the present invention, it will be appreciated that those skilled in the art may devise numerous other modifications and implementations that will fall within the scope and spirit of the principles disclosed herein. More specifically, within the scope of the present disclosure, drawings, and claims, a variety of variations and modifications may be made to the components or layout. In addition to variations and modifications made to the components or layout, other uses will also be apparent to those skilled in the art.

Claims

1. A method for preparing nano silver powder by electrolytic refining, characterized in that: An anion exchange membrane is used to separate an electrolytic cell into an anode chamber and a cathode chamber. A silver nitrate solution is contained in the anode chamber, and a silver ammonia solution is contained in the cathode chamber. The anode of the electrolytic cell is a soluble anode, and the cathode is a stainless steel or titanium plate. The electrolyte in the electrolytic cell is subjected to constant current electrolysis. During the electrolysis process, the electrolyte in the cathode chamber is separated and silver powder is collected before entering the anode chamber. The electrolyte in the anode chamber is separated from impurities before entering the cathode chamber, so as to realize the internal circulation of the electrolyte. The pH value of the silver nitrate solution is controlled at 1-2 by nitric acid, and the pH value of the silver ammonia solution is controlled at 7-8 by ammonia water. The cathode chamber Ag + The concentration is 5-10 g / L, Ag in the anode chamber + The concentration is higher than that of Ag in the cathode chamber + concentration; polyvinyl pyrrolidone is added to the silver ammonia solution as a dispersant at a concentration of 0.1 to 1 g / L, and ultrasonic oscillation is applied to the cathode chamber; the cathode current density is controlled to be 20 to 50 mA / cm 2 , the electrolysis temperature is 60-70℃.

2. The method for preparing nano silver powder by electrolytic refining according to claim 1, characterized in that: The anion exchange membrane is one of a polystyrene disulfonate membrane and a polyethylene sulfonate membrane.

3. The method for preparing nano silver powder by electrolytic refining according to claim 1 or 2, characterized in that: The device for preparing nano silver powder by electrolytic refining adopted in the method comprises an electrolytic cell, wherein the electrolytic cell is divided into an anode chamber and a cathode chamber by an anion exchange membrane, the lower outlet of the anode chamber is connected to a cathode liquid buffer tank through a filter, the cathode liquid buffer tank is connected to an upper inlet of the cathode chamber, the upper outlet of the cathode chamber is connected to an anode liquid buffer tank through a filter, and the anode liquid buffer tank is connected to an upper inlet of the anode chamber.

4. The method for preparing nano silver powder by electrolytic refining according to claim 3, characterized in that: The bottom outlet of the cathode liquid buffer tank is connected with a waste electrolyte tank.

Citation Information

Patent Citations

  • Method for producing nano-silver powder or nano-gold powder

    CN101314860A

  • Method for electrochemically aided preparation of silver powder with special form

    CN102418118A

  • Method for preparing micron-sized monodisperse silver powder based on electrochemical deposition method

    CN114540881A